1974
DOI: 10.1038/bjc.1974.4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-tumour Cell Mediated Immunity and Serum Blocking Factors in Cancer Patients by the Leucocyte Adherence Inhibition Test

Abstract: Summary.-The leucocyte adherence inhibition (LAI) test, previously described for the detection of cell mediated immunity and serum blocking factors associated with murine tumours, has now been adapted for use with human cancer patients. Blood leucocytes from these patients, mixed in vitro with antigenic extracts of tumours of the same type, had their normal adherence to glass surfaces diminished. This inhibition was reversed (blocked) by the addition of the patients' own sera. Both LAI and blocking were tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(37 citation statements)
references
References 13 publications
3
34
0
Order By: Relevance
“…The LAI Test [7,9] Equal volumes (0.1ml) of leucocyte suspension (2X106 cells), antigen solution and serum (when required) were mixed in small plastic tubes and incubated at 37 °C for 1 h with periodic shaking. Where serum was not included, medium was added to make the final volume 0.3 ml.…”
Section: Antigen Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LAI Test [7,9] Equal volumes (0.1ml) of leucocyte suspension (2X106 cells), antigen solution and serum (when required) were mixed in small plastic tubes and incubated at 37 °C for 1 h with periodic shaking. Where serum was not included, medium was added to make the final volume 0.3 ml.…”
Section: Antigen Solutionsmentioning
confidence: 99%
“…Firstly, an investiga tion of apparent non-reactivity ('tolerance') in contact hypersensitivity to dinitrochlorobenzene (DNCB) in guinea pigs revealed that non-reactive animals indeed possessed CMI to the hapten, as judged by macrophage migration inhibition (MMI) tests; these animals differed from hypersensi tive ones in the possession of a serum factor which blocked CMI in vitro [10]. Secondly, a rapid and simple technique, called leucocyte adherence inhibition (LAI), has recently been devised in our laboratory [9] and ap plied to the study of CMI and serum blocking factor in tumor immunity [7,8,17]. The time seemed opportune for the use of the new technique to study immune reactions in another situation where both reactivity and non-reactivity to antigens were observed: in acute and chronic dermatophytic infections.…”
Section: Introductionmentioning
confidence: 99%
“…The entire procedure requires only 3 -4 h to complete. Because of the brevity, simplicity, and the fact that tumor cells need not be separated, cultured or labelled, the original method has been improved in some ways and used to demonstrate tumor-specific reactivities of leukocytes from patients with breast [2,13), colorectal [11,17], pancreas [8] or prostatic can cer [18] or malignant melanoma [10,[14][15][16], The LAI microtest [9] is one of the improved methods. The original LAI technique by Holliday et al [1] requires careful floatation of a cover slip from the surface of a haemocytometer, but in the microtest the plate is only held in an inverted position to allow nonadherent cells to float off the bottom of the wells.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this pro perty of cells, the cellular leukocyte adherence inhibi tion (C-LAI) and humoral leukocyte adherence in hibition (H-LA1) tests were developed to study cellmediated or humoral immunoactivity during the ma lignant process [1][2][3]. It seems that the H-LAI tech nique being as effective as the C-LAI possesses further advantages.…”
Section: Introductionmentioning
confidence: 99%